STRATEGI GURU DALAM MEMBERIKAN PEMBELAJARAN PADA SISWA SLOW LEARNER KELAS III DI SDN 69 PALEMBANG - Putri Okviana, Eka; Murniviyanty, Liza; Puspita Sari Jaya, Melinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the strategies used by teachers in teaching slow learners at SDN 69 Palembang. The background of this study is based on the fact that each student has different learning abilities, which requires teachers to implement more effective learning strategies to ensure slow learners' success in learning. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that teachers implemented various learning strategies tailored to the needs of slow learners. These strategies include individualized approaches, simplifying learning materials, gradual repetition of material, the use of visual media, seating arrangements at the front of the class, and providing remedial classes for students who have not yet achieved learning mastery. These strategies still need to be developed in a more structured manner to optimize learning for slow learners.